Dinheiro, crédito e finanças: uma introdução a teoria monetária e financeira de Marx - Corazza, Gentil (2002)
The paper analyzes the nature of capitalist finances in Marx, from a conceptual point of view. Its main objective is to analyze the theoretical concepts of Marx's monetary and financial theory, such as the concept of money, credit money, capital money, finance capital and fictitious capital. It emphasizes the logical derivation and the structural complementation of all these concepts. The paper concludes by analyzing the logic and the contradictions which move the development of the credit system and the financialinstitutions.